Humanizing research: decolonizing qualitative inquiry with youth and communities - Paris, Django; Winn, Maisha T. (SAGE, 2014)
"What does it mean to conduct research for justice with youth and communities who are marginalized by systems of inequality based on race, ethnicity, sexuality, citizenship status, gender, and other categories of difference? In this collection, editors Django Paris and Maisha Winn have selected essays written by top scholars in education on humanizing approaches to qualitative and ethnographic inquiry with youth and their communities. Vignettes, portraits, narratives, personal and collaborative explorations, photographs, and additional data excerpts bring the findings to life for a better understanding of how to use research for positive social change."– Site de l'éditeur.
Le texte de Tuck, E. et Yang, K. W. (2014). “R-words: Refusing research” a été donné en lecture au cours POL4212.
Keywords: approches et analyses; cours; discipline; décolonialisme; hétérosexisme; intersectionnalité; inégalités; méthodologie; outils; pol4212; pour des recherches en milieux de pratiques; premier cycle; racisme; recherche qualitative; sciences de l'éducation; sexisme; systèmes d'oppressions